2021
DOI: 10.1007/jhep05(2021)261
|View full text |Cite
|
Sign up to set email alerts
|

Chiral massive news: null boundary symmetries in topologically massive gravity

Abstract: We study surface charges on a generic null boundary in three dimensional topological massive gravity (TMG). We construct the solution phase space which involves four independent functions over the two dimensional null boundary. One of these functions corresponds to the massive chiral propagating graviton mode of TMG. The other three correspond to three surface charges of the theory, two of which can always be made integrable, while the last one can become integrable only in the absence of the chiral massive gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 97 publications
3
59
0
Order By: Relevance
“…First of all, an additional corner potential ϑ 1 is necessary in order to obtain integrable charges. This is similar to what happens in Topologically Massive Gravity for a finite null boundary [52]. Second, there is another natural corner potential ϑ 2 which controls the Weyl part of the charges and the associated Heisenberg algebra.…”
Section: Corner Ambiguitiessupporting
confidence: 60%
See 4 more Smart Citations
“…First of all, an additional corner potential ϑ 1 is necessary in order to obtain integrable charges. This is similar to what happens in Topologically Massive Gravity for a finite null boundary [52]. Second, there is another natural corner potential ϑ 2 which controls the Weyl part of the charges and the associated Heisenberg algebra.…”
Section: Corner Ambiguitiessupporting
confidence: 60%
“…This is similar to the case studied in[52] where generic boundary conditions around a finite null surface were worked out in Topologically Massive Gravity. Therein, it was shown that it exists specific choices of slicing and of a corner ambiguity for which the non-integrability of the charges is only sourced by the physical flux passing through the boundary.…”
supporting
confidence: 60%
See 3 more Smart Citations